Supporting residents to care for a stoma independently. (2nd May 2019) - Burch, Jennie
Abstract : Older people have a higher chance of having a stoma formed, as the incidence of colorectal cancer and diverticular disease increases with age. It is important that they care for the stoma themselves, where possible. Jennie Burch explains how this is achieved.